The Development of STAD Cooperative Learning Tools to Improve Student Learning Outcomes on Sequences and Series Topic - Gunawan, Agus Indra; Nurtiyasari, Devi; Sukiyanto, Sukiyanto (Jurnal Pendidikan Matematika, 2022)
This study aims to develop a STAD cooperative learning tools that is able to improve students’ learning outcomes of 12th grade on the topic of series and sequences. This research is quasi-experimental research with preliminary development research conducted in two stages, namely learning tools development phase and experiment phase. The development phase follows plomp model that consists of five phases of development, namely: 1) preliminary investigation, 2) design, 3) realization, 4) test, evaluation, and revision, and 5) implementation. learning tools are developed in the form of: (1) lesson plan, (2) student worksheet, and (3) achievement test. While the experiments aim to determine the effectiveness of STAD cooperative learning by using developed learning tools and to compare students’ learning outcomes that taught by STAD cooperative learning with students’ learning outcome that taught by conventional learning. The results of this study showed that: (1) STAD cooperative learning tools have met the criteria for valid, practical, and effective learning tools, (2) STAD cooperative learning is effective to teach the topic of series and sequences, (3) the students’ learning outcomes that taught by STAD cooperative learning is significantly better than students’ learning outcomes that taught by conventional learning. STAD cooperative learning tools can be used as an alternative learning media on sequences and series topic. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran kooperatif tipe STAD yang dapat meningkatkan hasil belajar siswa kelas 12 pada materi barisan dan deret. Penelitian ini merupakan penelitian eksperimen semu yang didahului penelitian pengembangan yang dilaksanakan dalam dua tahap, yaitu tahap pengembangan perangkat dan tahap eksperimen. Tahap pengembangan perangkat menggunakan model plomp yang terdiri dari lima tahap pengembangan, yaitu: 1) investigasi awal, 2) desain, 3) realisasi, 4) tes, evaluasi dan revisi, 5) implementasi. Perangkat pembelajaran yang dikembangkan berupa: (1) Rencana Pelaksanaan Pembelajaran (RPP), (2) Lembar Kerja Siswa (LKS), dan (3) Tes Hasil Belajar (THB). Sementara itu, tahap eksperimen bertujuan untuk mengetahui keefektifan pembelajaran kooperatif tipe STAD dengan menggunakan perangkat pembelajaran yang dikembangkan sekaligus untuk membandingkan hasil belajar siswa kelas XII pada topik barisan dan deret yang diajar dengan pembelajaran kooperatif tipe STAD dengan hasil belajar siswa yang diajar dengan pembelajaran konvensional. Hasil penelitian ini menunjukkan bahwa: (1) perangkat pembelajaran kooperatif tipe STAD telah memenuhi kriteria perangkat pembelajaran yang valid, praktis, dan efektif, (2) pembelajaran kooperatif tipe STAD efektif untuk mengajarkan materi deret dan barisan, (3) Hasil belajar siswa yang diajar dengan pembelajaran kooperatif tipe STAD secara signifikan lebih baik dibandingkan dengan hasil belajar siswa yang diajar dengan pembelajaran konvensional. Perangkat pembelajaran kooperatif STAD dapat digunakan sebagai media pembelajaran alternatif pada topik barisan dan deret.